2013
DOI: 10.3109/10428194.2013.779687
|View full text |Cite
|
Sign up to set email alerts
|

Renewed interest in the role of consolidative radiotherapy in advanced stage diffuse large B-cell lymphoma

Abstract: Diffuse large B-cell lymphoma (DLBCL) represents the most common subtype of non-Hodgkin lymphoma (NHL) in the United States, and two-thirds of these patients will present with advanced stage (stage III-IV) disease. Although radiation therapy (RT) alone was the first curative therapy for limited stage DLBCL, the advancement of combination chemotherapy with cyclophosphamide, doxorubicin, vincristine and prednisone (CHOP) with the addition of the anti-CD20 antibody rituximab became the cornerstone of current mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
1
12
0
1
Order By: Relevance
“…The ongoing Unfavorable Low-Risk Patients Treated with Densification of R-Chemo Regimens (UNFOLDER) trial (clinical trial registry: NCT00278408) featuring a 2x2 randomization comparing R-CHOP -21 and 14 as well as RT or no RT to ≥7.5 cm bulky disease will eventually help guide decisions on RT. The arms without RT were recently closed on interim analysis suggesting some benefit to RT[26]. Results from this study will further shed light on management of DLBCL patients.…”
Section: Resultsmentioning
confidence: 99%
“…The ongoing Unfavorable Low-Risk Patients Treated with Densification of R-Chemo Regimens (UNFOLDER) trial (clinical trial registry: NCT00278408) featuring a 2x2 randomization comparing R-CHOP -21 and 14 as well as RT or no RT to ≥7.5 cm bulky disease will eventually help guide decisions on RT. The arms without RT were recently closed on interim analysis suggesting some benefit to RT[26]. Results from this study will further shed light on management of DLBCL patients.…”
Section: Resultsmentioning
confidence: 99%
“…It compares 2 schedules of RCHOP (RCHOP-21 or -14) with or without consolidative RT in aggressive B-cell NHL patients [28]. Relatively young patients (aged 18-60 years), initially with bulky disease (≥7.5 cm) and/or qualifying extranodal involvement, who achieved CR to 6 cycles of RCHOP-14 or -21 will be further randomized to observation versus consolidative RT.…”
Section: Discussionmentioning
confidence: 99%
“…[47] In summary, these trials suggested that combined modality treatment with RT and lesser courses of CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisone) was at least as efficacious as full course of chemotherapy. [8] GELA 93-4 looked specifically at older patients and found that RT with CHOP had similar survival rates as CHOP alone [4] and suggested that RT for elderly patients can be omitted all together.…”
Section: Introductionmentioning
confidence: 99%